Utilization of Information Sources by SRI growers - Meenakshi Gabhane , M. K. Dubey, D. K. Singh; Anjani Kumar (Indian Journal of Extension Education, 2015)
The information sources play a key role in ensuring food security and sustainable agriculture. The demonstration, agricultural scientist, friend, extension worker, training, television, radio, relative etc. are the main source of information by creating socio information support system to identify the problem of the SRI farmers so that the need based information through information sources may be provided and also to established its utility among SRI farmers there by resulting. The present study was carried out to know the utilization of information sources by SRI growers in Balaghat block of District Balaghat Madhya Pradesh with 120 SRI farmers of Balaghat block. It was found that the most of the respondents they were utilized the information sources mostly respect to SRI method of paddy cultivation, In case of individual contact methods Agricultural scientists and Rural Agril. Extension officers were the main source of information. In case of group approach Demonstration, Training and Lecture were the main source of information and in the case of mass approach Television and Radio were the main source of information utilized by the SRI growers.